Agrochemical use patterns among fresh produce farmers in Nakuru County, Kenya: Examining the instigators (African Journal of Science, Technology and Social Sciences, 2025)
Agriculture is the most important economic activity in Kenya, despite only 10.2% of the total land cover being arable. The agriculture sector contributes 51 percent of Kenya’s GDP, 26 percent directly and 25 percent indirectly, accounting for 60 percent of employment and 65 percent of exports (KNBS, 2024). To achieve optimal production in the agricultural sector, agrochemicals play a significant role. On average 12,983 tons of agrochemicals are imported in to the country annually with a total value of KES 10.7 billion. More agrochemical volumes are required over time resulting in a vicious cycle between agrochemical use dependency and worsening health and climatic conditions. This study sought to determine the agrochemical use practices among Fresh Produce Farmers in Nakuru County, Kenya and their drivers. The study design was a community based cross-sectional analytic and descriptive study. The target population included Fresh Produce Farmers residing in Nakuru County for at least two years routinely applying agrochemicals in their daily occupational activities. A two-stage sampling technique, using probability proportional to size (PPS), was applied to select four sub-counties: Njoro, Kuresoi North, Molo, and Bahati. A total of 388 respondents were sampled using Cochran’s formula with a 10% non-response adjustment. Quantitative data were collected using structured questionnaires, while qualitative insights were gathered through focus group discussions and key informant interviews. Data were analyzed using SPSS v28 for descriptive and inferential statistics, and NVivo for thematic analysis. The findings revealed a significant association between awareness of pest pressure and resistance of agrochemicals and decision-making on volume and frequency of agrochemical usage. 87% of respondents who used recommendations from experts were aware of the potential environmental impacts of agrochemicals. 72% and 48% of those who used previous experience and those using recommendations from other farmers were also aware of the potential environmental impacts of agrochemicals, respectively. Fresh produce farmers who have realized extreme weather patterns use fewer methods of applying agrochemicals. The Ministry of Agriculture and the Ministry of Environment, Climate Change, and Forestry need to work collaboratively to support fresh produce farmers in Nakuru County in public extension services, which will play a critical role in increasing the protective use of agrochemicals. Public extension services will shift the decision-making habits of the farmers to ensure that they use recommendations from the extension services in all their farming practices.
Keywords: Agrochemical use Patterns; Fresh Produce Farmers; Nakuru County